The roots of demotivation in studying English: Sociocultural values among students in a rural area - La Dunifa (Universitas Syiah Kuala, 2024)
This confessional ethnographic study strives to reveal the sociocultural values that are suspected as trigger factors of students demotivation in studying English. The study was conducted in a junior secondary school in the Miendogunu Village, Buton, Sulawesi, one of the rural areas in Indonesia. There were 32 participants in this study (21 students, nine parents, an English teacher, and the school principal). This research relied on data gathered through in-depth interviews and observation. The data analysis covered taxonomic analysis, componential analysis, and thematic analysis, specifically aimed at discerning inter-domain connections and how those connections relate to the larger cultural landscape. The results revealed three interrelated themes, namely: ethnocentric stereotype (the tendency to look down on English because it is a foreign culture), the skeptical view (doubt toward the worth of English), and slow living lifestyle (a lifestyle that encourages a slower approach to aspects of everyday life). These three sociocultural values are investigated as the trigger factors that have turned the EFL students halfhearted toward English. A complementary strategy focused on changing students mindsets is needed; they need to be aware that English, nowadays, is the language of technology and has become an added and preferable qualification for employability. To a certain degree, it is important to impart awareness to the villagers regarding the significance of preserving their indigenous culture. However, a cautious approach is necessary, as isolating themselves entirely from external cultural influences may be deemed an unwise course of action.